A Decade Under the Influence - Demme, Ted; LaGravenese, Richard; Jannelli, Anthony; Smith, Clyde W. (Video Collection International, 2004)
The 1970s was an extraordinary time of rebellion, and of questioning every accepted idea. As political activism, the sexual revolution, the woman's movement, and the music revolution contributed to social unrest across the country, American cinema witnessed the emergence of a new generation of filmmakers. Galvanized by a new freedom of expression, these ground-breaking artists began targeting their films towards a new kind of audience, with stories that reflected the ever-changing reality of the era. A love letter to an amazing era in film, "A Decade Under the Influence" enlists a cast of pioneering writers, directors and actors to talk about the time, their films and their colleagues. A virtual cinematic scrapbook of the decade, filmmakers Richard La Gravenese and the late Ted Demme include a cornucopia of clips from such classics as "Easy Rider", "The Godfather" and "Coming Home". The result is a fantastic celebration of the artists and films that left a vital and lasting stamp on America's national cinema and identity. [www.dvdempire.com]